Arabic Language Teachers' Use of TikTok Media to Improve Generation Z's Speaking Skills at Madrasah - Rizieq, Dhea Ratu; Sauri, Sofyan; Khalid, Shofa Mustafa; Nurmuhammadovna, Ro‘ziboyeva Nigora (Study Program of Arabic Language Teaching, 2025)
This study examines using TikTok as a learning medium by Arabic language teachers to improve Generation Z students' speaking skills (maharah kalam) at Al-Ikhlas Islamic School. The research subjects include Arabic language teachers and Generation Z students using TikTok. The population in this study was teachers and students at Madrasah Al-Ikhlas who were taking Arabic language classes. The sample was selected purposively, consisting of 1 Arabic teacher and 11 Generation Z students who actively use the TikTok app as a learning medium. This study adopts a qualitative approach using observation, interviews, and questionnaires, which were analyzed through thematic analysis. The results indicate that TikTok was chosen because it is engaging, easy to understand, and enhances student participation in the learning process. Teachers utilize short video content to present material more varied and less monotonously. Despite challenges such as limited internet access and device availability, using TikTok has proven to support more interactive Arabic language learning.